The Role of Cultural Capital in Strengthening the Relationship between Need and Demand for Contraceptive Devices and Drugs in Several Cultural Areas in Indonesia - Mahalia, Lamia Diang; Supriyanto, Stefanus (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Acceptor’s decision to use particular contraceptive devices/drugs is influenced by cultural capital. Cultural capital has three forms: Embodied state, objectified state, and institutionalized state. AIM: This study aimed to analyze the influence of culture as a moderating variable on the relationship between need and demand for contraceptive devices/drugs in several cultural areas in Indonesia. METHODS: This observational study used a cross-sectional design. The criteria for research subjects were: (1) Women at child-bearing age who were currently using contraceptive devices/drugs of IUD, implants, pills, or injections; (2) Aged 15–49 years old; and (3) Indonesian citizens who come from Dayak and Javanese cultural areas. Sampling was performed using the multistage random sampling technique. The data were obtained through questionnaire and analyzed using the Partial Least Square (PLS) statistical test. RESULTS: The results of statistical tests showed that there was a significant relationship between the need and use of contraception (p = 0.000). The amount of influence between need and demand for contraceptive devices/drugs contraceptives reached 79.2% (R2 = 0.7 92). It was found that cultural capital (objectified state and institutionalized state) did not have a significant relationship with demand (p = 0.113) and had an insignificant moderating effect value (p = 0.722). Thus, it can be interpreted that cultural capital (objectified state and institutionalized state) is a variable that has the potential to become a moderating variable that can affect the strength of the relationship between need and demand. The original sample moderating effect value was positive at 0.017, meaning that the cultural capital moderating variable can strengthen the relationship between the need and demand for contraceptive devices/drugs. CONCLUSION: There is a significant relationship between need and demand for contraceptive devices/drugs. Culture capital (objectified state and institutionalized state) is a variable that has the potential to become a moderating variable that can strengthen the relationship between the need and demand for contraceptive devices/drugs. Therefore, a cultural approach is needed so that acceptors can use contraceptive devices/drugs that suit their needs.